Untargeted metabolomic analysis uncovers metabolic variability of four Bifidobacterial strains for probiotic development - Liu, Kailong; Yao, Guoqiang; Yang, Zhan; Huang, Tian; Kwok, Lai-Yu; Zhang, Heping (Frontiers in Microbiology, 2025)
Bifidobacterium species are essential members of the human gut microbiota, playing crucial roles in host health. Variations in the metabolic functions of different Bifidobacterium strains can have distinct health effects, making it essential to understand their metabolic characteristics for the development of targeted probiotic formulations. In this study, we cultivated four selected Bifidobacterium strains from three species: Bifidobacterium animalis subsp. lactis BB-69, Bbm-19, Bifidobacterium brevis BX-18, and Bifidobacterium longum subsp. infantis B8762. We conducted an untargeted comparative metabolomic analysis to investigate the intracellular metabolic profile and functional activities of these strains. A total of 1,340 metabolites were identified, revealing significant variations in their metabolomic profiles. Notably, Bifidobacterium animalis subsp. lactis Bbm-19 showed higher activity in amino acid biosynthesis, while Bifidobacterium animalis subsp. lactis BB-69 exhibited increased activity in secondary bile acid biosynthesis and alpha-linolenic acid metabolism. Bifidobacterium longum subsp. infantis B8762 demonstrated enhanced activity in polycyclic aromatic hydrocarbon degradation, vitamin digestion and absorption, and galactose metabolism. Bifidobacterium breve BX-18 was more active in tryptophan metabolism and pentose and glucuronate interconversions. Targeted analyses of specific metabolites further revealed strain-specific metabolic pathways. This study systematically elucidates the metabolic profile differences among the four investigated Bifidobacterium strains at the untargeted metabolomic level, providing valuable insights into their metabolic characteristics and potential applications in probiotic development.